Recombinant AAV batch profiling by nanopore sequencing elucidates product-related DNA impurities and vector genome length distribution - Florian Dunker-Seidler; Kathrin Breunig; Magdalena Haubner; Florian Sonntag; Markus Hörer; Rebecca C. Feiner (Molecular Therapy: Methods & Clinical Development)
During production, recombinant adeno-associated virus (rAAV) capsids are equipped with heterogeneous genetic payloads including undesired DNA impurities as well as truncated vector genomes. Comprehensive analysis of encapsidated DNA by long-read next-generation sequencing is destined to guide platform optimization and provide crucial insights into safety of gene therapies. We used nanopore sequencing for in-depth profiling of an rAAV9 batch produced using our proprietary split two-plasmid system in a 50-L bioreactor. We compared three methods for single-strand to double-strand DNA conversion and their impact on the sequencing data. We observed a distinct library size profile but comparable impurity distribution. We contrasted recent nanopore sequencing advancements such as the V14 chemistry and dorado basecalling software with the widespread V9 chemistry and detected a markedly increased read quality. Our data highlight a high vector batch quality with low plasmid-derived and host cell DNA impurities of random origin, critical for mitigating associated safety risks. Finally, we compared nanopore data with orthogonal SMRT sequencing data and observed a higher base quality, but largely similar length and impurity profiles. Taken together, nanopore sequencing is a state-of-the-art method for comprehensive, in-depth rAAV vector batch analysis during all stages of gene therapy development.